Anetoderma - A hidden presentation of lepromatous leprosy - Sruthi Kareddy; C Nikitha; P Mamatha (Wolters Kluwer Medknow Publications, 2023)
Anetodermas is a rare disorder of connective tissue associated with a circumscribed area of slack skin associated with focal loss of elastin. This correlates with the clinical observation of atrophy and "buttonhole" sign or herniation phenomenon. Secondary anetoderma has multiple causes, which should be looked for, out of which lepromatous leprosy is rare. It is important to identify infective conditions like leprosy not only for the individual but also epidemiological control as well. We report a case of Lepromatous leprosy presenting as anetoderma.